Biofuel derived from enzymatic degummed linum usitatissimum seed oil : as a potential resource for diesel engine (Bangladesh Journal of Scientific and Industrial Research, 2014)
A bio-fuel derived from enzymatic degummed Linum usitatissimum seed oil (EDLO). We applied response surface methodology in order to optimize the reaction conditions of degumming process using microbial enzyme (Licitase ultra) in Linum usitatissimum seed oil, Enzyme dosage, temperature and reaction time were important determining factors affecting oil degumming. Optimum operating conditions were found to be reaction time of 5 h, enzyme dosage of 1.6 wt% and temperature of 50°C at pH 5. At this optimum condition point the phosphorus content of degummed oil were found to be 7.8 mg/kg. This study also discusses the EDLO-diesel fuel blends as a potential source for blend production. Furthermore, the blends of various proportions of EDLO:diesel,25:75, 35:65, 45:55 and 55: 45 were prepared, characterized and compared with diesel fuel. The fuel properties of EDLO25 diesel fuel blend was found comparable to those of diesel on the basis of experimental analysis.. DOI: http://dx.doi.org/10.3329/bjsir.v49i1.18849 Bangladesh J. Sci. Ind. Res. 49(1), 13-24, 2014